2016
DOI: 10.1038/nm1016-1192a
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: Adjuvant-dependent innate and adaptive immune signatures of risk of SIVmac251 acquisition

Abstract: In the version of this article initially published online, an affiliation for Luca Schifanella was omitted and there was an error in the description of the phenotypic analyses of plasmablasts in the Online Methods. The error has been corrected for the print, PDF and HTML versions of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…At 10 and 60 days post-boost, blood was harvested by submandibular bleeding to determine adaptive and memory humoral HIV-1 gp140-specific immune responses, respectively. One week post-second bleed, animals from all groups (1)(2)(3)(4)(5)(6)(7)(8) were boosted with 10 µg of gp140(97CN54) protein + 5 µg of MPLA as adjuvant by i.m. route and 10 days post-protein boost, mice were sacrificed and spleens and draining lymph nodes (DLNs) processed for ICS assay and sera harvested for ELISA to determine both cellular and humoral responses against HIV-1 gp140 protein, respectively.…”
Section: Mouse Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…At 10 and 60 days post-boost, blood was harvested by submandibular bleeding to determine adaptive and memory humoral HIV-1 gp140-specific immune responses, respectively. One week post-second bleed, animals from all groups (1)(2)(3)(4)(5)(6)(7)(8) were boosted with 10 µg of gp140(97CN54) protein + 5 µg of MPLA as adjuvant by i.m. route and 10 days post-protein boost, mice were sacrificed and spleens and draining lymph nodes (DLNs) processed for ICS assay and sera harvested for ELISA to determine both cellular and humoral responses against HIV-1 gp140 protein, respectively.…”
Section: Mouse Immunizationmentioning
confidence: 99%
“…To date, only one HIV-1 phase III clinical trial (Thai RV144 trial) has reported some efficacy (31.2%) against HIV-1 acquisition (5). At present, the evaluation of the vaccineinduced immune correlates of protection in non-human primates (NHPs) and in humans, such as broadly neutralizing antibodies (bNAbs), non-neutralizing antibodies targeting the variable loops 1 and 2 (V1/V2) of the HIV-1 envelope (Env), Env-specific polyfunctional antibodies and T cell responses, are guiding different HIV-1 vaccine approaches and regimens (6)(7)(8). The RV144 regimen, novel vaccines based on adenovirus vectors, mosaic immunogens, optimized gp140 proteins (such as HIV-1 Env SOSIP trimers) and passive administration of monoclonal antibodies are among the most recent strategies for HIV-1 prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The modest efficacy of the RV144 HIV-1 vaccine candidate and the analyses of vaccine-induced immune correlates of protection in humans and NHP models [ 8 , 9 , 10 ] are currently guiding the development of novel HIV-1 vaccines [ 71 ]. Preventative and therapeutic strategies have been pursued and investigated into test-of-concept clinical trials with the aim to provide protection against HIV-1 [ 72 , 73 ].…”
Section: Current Hiv-1 Vaccine Approachesmentioning
confidence: 99%
“…So far, only one HIV-1 vaccine clinical trial—the Thai Phase III RV144—demonstrated some efficacy of vaccination against HIV-1 acquisition [ 7 ]. Currently, the analyses of vaccine-induced immune correlates of protection in humans and non-human primate (NHP) models are guiding different HIV-1 vaccine approaches [ 8 , 9 , 10 ]. In this review, we provide a general overview of the recent advances in HIV-1 vaccine development, with a focus on the immunological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to date, HIV-1 vaccine candidates have largely been unsuccessful in human clinical trials. Despite promising preclinical results in nonhuman primate (NHP) studies (1)(2)(3)(4)(5)(6), the majority of candidate vaccines have failed to elicit similarly potent immunogenicity or protection when subsequently tested in humans (7)(8)(9)(10). The development of a small-animal model capable of supporting HIV-1 infection and recapitulating HIV-1-specific human immunity may help accelerate the design and testing of next-generation HIV-1 vaccines.…”
mentioning
confidence: 99%